Man, morality, and society in Bernard Mandeville’s thought - Ślęczek-Czakon, Danuta (Folia Philosophica, 2001)
The article is devoted to a presentation of the persona and the ideas of Bernard Mandeville. This author is frequently omitted in the history of ethics, and if his ideas are remembered, then only in a fragmentary way. Mandeville's output deserves a higher evaluation - his analyses of man, morality, and society were innovative in the 17lh century, they are achievement of the English Enlightenment, and the significance of his anthropology goes beyond the epoch in which he lived.